Bridging resilience and mathematics success: the mediating role of teacher emotional support - Irene O. Mamites; Jhamm M. Olila; Wendy Q. Aliviano; Gley S. Arañas; Quenie R. Abesia; Emerson D. Peteros (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study investigated the mediating role of teacher emotional support (TES) in the relationship between academic resilience (AR) and mathematics performance (MP) among 563 randomly selected Grade 7 students from public secondary schools in Mandaue City, Cebu, Philippines. Employing a descriptive correlational design, data were collected through an adopted questionnaire—academic resilience scale (ARS-30), emotional support scale, and the students’ first quarter mathematics grade. The data collected were analyzed using frequency, percentage, weighted mean (WM), standard deviation (SD), Pearson r, and multiple regression analysis. Findings indicated high AR, very high TES, and satisfactory MP. Mediation analysis revealed that TES partially mediates the positive association between AR and MP. This analysis offers valuable guidance for educators, researchers, and policymakers in creating supportive learning environments that build AR and enhance TES, leading to better MP.